The Role of Field Work Practice and Organizational Activities in Shaping The Work Readiness of Accounting Education Students - Suranto, S; Purwaningsih, Mei Eka (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the effect of Field Work Practice (KKL) and organizational involvement on the work readiness of students in the Accounting Education Study Program at Universitas Muhammadiyah Surakarta. The research employed a quantitative method using questionnaires distributed to 38 students from the 2021 cohort. The prerequisite tests included normality, heteroscedasticity, multicollinearity, and the coefficient of determination. Data were analyzed using the t-test, F-test, and multiple linear regression. The findings revealed that both field work practice and organizational involvement, simultaneously and partially, had a significant effect on students' work readiness. Students who actively participated in field activities and organizational programs were more likely to develop the knowledge, skills, and self-confidence required to enter the workforce. These findings strengthen the theory that work readiness is shaped not only by cognitive aspects but also by social experiences and hands-on practice. Therefore, higher education institutions need to provide greater support for student organizational activities and the implementation of field work practice that is relevant to the study program.